A smart window with angular-selective absorption for automotive. (April 2023) - An, Chan-Heon; Lee, Jae-Hwan; Han, Chan-Hee; Oh, Seung-Won
Abstract: The guest host liquid crystal (GHLC) cell exhibits angular-selective absorption properties owing to the absorption anisotropy of the dichroic dye. The vertically aligned GHLC cell can absorb oblique incident light while providing a clear normal view. However, if the installation angle of the window changes, the transmittance in the normal view decreases. In this study, we proposed a GHLC cell that can be applied to windows at various installation angles. We adjusted the pretilt angle by considering the path length of the light to optimize a clear normal view. For the automotive windshield (installation angle of 45°), we set the pre-tilt angle to 55°, and the transmittance of the proposed LC cell in normal and oblique views was 70.8% and 50.8%, respectively. Therefore, the proposed cell can provide a clear normal view for a driver while blocking the oblique incident light, which causes sun glare. Highlights: We propose a guest-host liquid crystal cell that changes the transmittance by incident angle. We propose a cell that can be applied to windows at various installation angles. The proposed LC cell can provide a transparent state while blocking the oblique incident light, which causes sun glare.